Ethnographic methods - O'Reilly, Karen (London : New York : Routledge, 2012)
This new edition of Karen O'Reilly's popular Ethnographic Methods provides a comprehensive and accessible introduction to the technical, practical and philosophical issues that arise when employing traditional and innovative research methods in relation to human agents. Using a wide range of case studies and source material to illustrate the dilemmas and resolutions that an ethnographic researcher may encounter, this textbook guides the reader from the initial design and planning stages through to the analysis and writing-up. It explores the historical and philosophical foundations of ethnogra.
Includes bibliographical references and index.
Keywords: Ethnology -- Philosophy; Ethnology -- Comparative method